Combining Impedance Spectroscopy and Information Visualization Methods to Optimize the Detection of Carbendazim Using Layer-by-Layer Films - Furini, Leonardo Negri; Fernandes, José Diego [UNESP]; Vieira, Douglas Henrique [UNESP]; Morato, Luis Fernando do Carmo [UNESP]; Alves, Neri [UNESP]; Constantino, Carlos José Leopoldo [UNESP] (MDPI, 2023)
Usually, electronic tongues (e-tongue) do not require specific interactions to discriminate aqueous solutions. Among the several factors which determine the electrical properties of sensing units, the interactions between liquids and interfaces have a crucial role. Here, we explore the interaction between dioctadecyldimethylammonium bromide (DODAB) lipid and carbendazim (MBC) pesticide in an e-tongue to discriminate different MBC concentrations in aqueous solutions. The sensing units were fabricated of gold interdigitated electrodes (IDEs) coated with layer-by-layer (LbL) films of DODAB and nickel tetrasulfonated phthalocyanine (NiTsPc), perylene and 1,2-dipalmitoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (DPPG), namely (DODAB/NiTsPc)5 and (Perylene/DPPG)5, respectively. Besides, a bare electrode also constituted the e-tongue to distinguish MBC concentrations from 1.0 × 10−7 up to 1.0 × 10−10 mol L−1, by impedance spectroscopy. In addition, the experiment was optimized using two IDE geometries. The LbL films were manually fabricated obtaining linear growth monitored via UV-Vis absorption spectroscopy. Optical images associated with chemical mapping reveals the presence of small aggregates in the DODAB/NiTsPc LbL film surface. Although the e-tongue was able to discriminate all MBC concentrations by means of the interactive document map (IDMAP), only the sensing unit covered with DODAB/NiTsPc LbL film presented a satisfactory response. According to the equivalent circuit, the main contribution arises from the bulk and film surface due to the interaction between DODAB and MBC, indicating THE sensitivity of the sensing unit. Finally, the adsorption of MBC molecules onto the film surface induced an irreversible process, although there are some frequencies at which the sensing unit response seems to be reversible, as shown by parallel coordinates.
Keywords: carbendazim; e-tongue; impedance spectroscopy; information visualization; LbL films